2022
DOI: 10.18502/jri.v23i3.10005
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Mitochondrial Translocator Protein and Voltage-Dependent Anion Channel-1 in Granulosa Cells with Estradiol Levels and Presence of Immature Follicles in Polycystic Ovary Syndrome

Abstract: Background: Granulosa cells (GCs) play key roles in oocyte maturation by providing required estradiol (E2). Since the presence of immature oocytes has been reported in cases with polycystic ovary syndrome (PCOS), in this study, the levels of mitochondrial membrane transporter proteins involved in E2 synthesis were determined. E2 concentration and parameters of oxidative status were also measured in follicular fluids of PCOS women.  Methods: Forty-three women with PCOS and 43 healthy women who were candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The only discrepancies in metabolic outcomes came from two conflicting reports on VDAC1. One study, using a rat PCOS model, reported higher VDAC1 protein levels, whereas another study, using GCs from PCOS patients, reported lower VDAC mRNA levels and immunocytochemical staining [53,67]. The differences may be due to species differences or gene and protein expression differences.…”
Section: Granulosa Cellmentioning
confidence: 99%
“…The only discrepancies in metabolic outcomes came from two conflicting reports on VDAC1. One study, using a rat PCOS model, reported higher VDAC1 protein levels, whereas another study, using GCs from PCOS patients, reported lower VDAC mRNA levels and immunocytochemical staining [53,67]. The differences may be due to species differences or gene and protein expression differences.…”
Section: Granulosa Cellmentioning
confidence: 99%